What about Education and Schooling for Sustainable Development? - Pérez de Villarreal, Maider (Advances in Social Sciences Research Journal, 2015)
Schooling as a form of formalized indoctrination has come to an end. In the new global and (g)local order a new context of interrelations re-shapes school organization searching for new spaces and new nested niches to perform key ecological principles of sustainability and community participation. In this paper, we get to sustainability from ecological premises contextualize together with educational development premises. We clarify the real links of both to give a context to what it means looking at school education from progressive principles, which resumes to look at each one`s (country or human) history, conditions for development, in order to do the best for growing, by not accommodating the system of education to strange external pressures which pretend to uniformize, fragmentize and exclude.